Where do MNEs expand production: Location choices of the pharmaceutical industry in Europe after 1992 - Frances P. Ruane; Xiaheng Zhang (The Economic and Social Research Institute (ESRI), 2007)
Differences in regulations, technical standards and national medical cultures across EU member states created a highly segmented pharmaceutical market in Europe prior to the implementation of the Single Market Programme. The subsequent reduction in non-tariff barriers to trade would be expected to have an impact on where pharmaceutical multinationals locate production within the EU. Using discrete-choice models, we study the determinants of multinationals' location choices in terms of expanded production at existing facilities. Our results support the findings of New Economic Geography models that predict reduced rather than increased agglomeration in the face of trade-cost reductions.
Keywords: F15; F23; R12; 330; economic geographic; location choice; discrete choice models; European integration; FDI; Europäische Integration; Standortwahl; Direktinvestition; Klein- und Mittelunternehmen; Pharmazeutische Industrie; Diskrete Entscheidung; Wirtschaftsgeographie; Schätzung; EU-Staaten